2015
DOI: 10.3109/00207454.2014.994063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different doses of near infrared light on dopaminergic cell survival and gliosis in MPTP-treated mice

Abstract: We have used the MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) mouse model to explore whether (i) the neuroprotective effect of near infrared light (NIr) treatment in the SNc is dose-dependent and (ii) the relationship between tyrosine hydroxylase (TH)+ terminal density and glial cells in the caudate-putamen complex (CPu). Mice received MPTP injections (50 mg/kg) and 2 J/cm2 NIr dose with either 2 d or 7 d survival period. In another series, with a longer 14 d survival period, mice had a stronger MPTP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Our experimental paradigm of simultaneous administration of MPTP insult and therapeutic application was similar to that of previous studies on animal models of PD . This paradigm is unlike clinical reality, where there is cell loss prior to therapeutic intervention.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Our experimental paradigm of simultaneous administration of MPTP insult and therapeutic application was similar to that of previous studies on animal models of PD . This paradigm is unlike clinical reality, where there is cell loss prior to therapeutic intervention.…”
Section: Methodsmentioning
confidence: 95%
“…Three monkeys had an optical fiber implant (but not activated) into the midbrain (see below), whereas 2 were left intact. A control group exposed to NIr was not included, because we have published previously that NIr has no impact on the survival and function of cells in normal brains . Given the consistency of these results, together with the rareness of primate tissue and the ethical considerations to reduce the number of primates used, we felt that the extra control group was redundant and not justified in our study. MPTP (n = 11): monkeys were administered 1.5mg/kg MPTP over 5 days (n = 6) or 2.1mg/kg over 7 days (n = 5); 10 of these monkeys were left intact, and 1 had an optical fiber implant (not activated). MPTP‐NIr (n = 9): monkeys were administered MPTP as above, in conjunction with optical fiber implants delivering NIr over 5 (total dose of 25J; n = 5) or 7 days (total dose of 35J; n = 4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent researches support the ability of light to penetrate the brain tissue and exert biological effects on photoacceptor molecules present in central nervous system structures . Several studies have shown its potential benefits in retinal diseases, stroke, neurodegeneration, neuromuscular disorders, and memory and mood disorders . In addition, the increase of the pain threshold in the right hindpaw of mice (measured by von Frey filaments) was demonstrated after photobiomodulation with infrared (810 nm) applied to different anatomical locations.…”
Section: Discussionmentioning
confidence: 94%